Informational Heredogram: a way to combat disinformation - Souza, Osvaldo de (2024)
In this text we discuss issues related to the organization and representation of knowledge to propose a theoretical-methodological contribution to positively impact the quality of information. Characterized as qualitative research of exploratory type with a bibliographic survey about coding, conceptual models and structuring patterns of bibliographic data, highlighting BIBFRAME, RDA, RDF and OWL, were explored, which were combined to define a new theoretical-methodological approach called Informational Heredogram with application in documents and texts coming from WEB information sources and recorded knowledge typical of library documents. Results obtained has properties of a taxonomic structure which simultaneously produces trustable information about documents and their respective contents. It considers the attribution of a Semantic Digital Object Identifier (SDOI) to be used in association with the Digital Object Identifier (DOI) or replacing it. The Informational Heredogram foresees the incorporation of active functional elements for the automatic production, with or without human supervision, of semantic elements regarding the contents of the texts. The proposal obtained in the works introduces elements to mitigate problems related to disinformation and fake news and adds elements from natural language processing (NLP), computational intelligence (CI) and artificial intelligence (AI).